2017
DOI: 10.21767/2471-9668.100031
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of a Protocol for Quantitative Evaluation of Anti-Aerosolized Influenza Virus Activity by Vapors of a Chemically-Characterized Essential Oil Blend

Abstract: The aim of this research is to standardize the conditions of a constructed impinger, enabling to evaluate quantitatively the anti-aerosolized H9N2 avian influenza virus (AIV) activity by vapors of a chemically-characterized essential oil blend. The standardization resulted in 100% recovery of the aerosolized H9N2 virus when the impinger's conditions were set at aerosolized viral particles count of 1.2 × 10 6 /c.c. of Tryptose Phosphate Broth, temperature of 35°C, average micelle diameter of 44.3 μm, negative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Earlier studies [ 24 , 44 ] corroborate with these antiviral findings. The IBV development was totally limited by n -hexane extract having 0 HA titer.…”
Section: Discussionsupporting
confidence: 75%
“…Earlier studies [ 24 , 44 ] corroborate with these antiviral findings. The IBV development was totally limited by n -hexane extract having 0 HA titer.…”
Section: Discussionsupporting
confidence: 75%
“…In a standardized protocol for quantitative evaluation of antiaerosolized AIV-A H9N2 activity by vapors of a well-characterized EO blend (using constructed impingers/glass chambers), Kumosani et al [65] showed that in contrast to the control (viral particles count: 1.2 × 10 6 /cm 3 ), within 1.5 min of contact time, a vaporized EO blend (equivalent volumes of eucalyptus oil with 42.2 % 1,8-cineole and peppermint oil with 48.7 % menthol) reduced the virus titer (aerosolized viruses) by about 84.6 % at a concentration of 1.0 × 10 −4 µL EO/µL air volume.…”
Section: Avian Influenza Virusmentioning
confidence: 99%
“…Based on the amino acid sequence spanning the cleavage site of the HA protein, AIVs are phenotypically distinguished into low-pathogenic avian influenza virus (LPAIV) and high-pathogenic avian influenza virus (HPAIV) (Sultan et al, 2017). LPAIVs have mono or dibasic cleavage sites at their HA cleavage site, allowing only proteases (trypsin-like) to cleave them in the respiratory and digestive systems and are characterized by low pathogenicity as measured by the intravenous pathogenicity index (Kumosani et al, 2017). On the other hand, HPAIVs have polybasic cleavage sites that allow them to replicate in various organs, including vascular endothelium and perivascular endothelial cells resulting in high pathogenicity in chickens (Ali et al, 2021).…”
Section: Introductionmentioning
confidence: 99%